Exploration and firms’ innovative performance – How does this relationship work? - G. P. Moreira, Frederico; V. Torkomian, Ana Lúcia; J. C. C. Soares, Thiago (Review of Business Management, 2016)
Purpose – The main purpose of this paper is to analyze (1) the relationship between a firm’s exploration strategy and its innovative performance, and (2) whether its absorptive capacity (AC) moderates this relationship. Design/methodology/approach – We adopted an econometric approach, using secondary data. We synchronized two databases – Compustat and USPTO –, from which we extracted common data concerning 275 biopharmaceutical firms for the period between 1990 and 2003. We used negative binomial regression to analyze data. Findings – The exploration strategy positively influences firms’ innovative performance. However, excessive emphasis on this strategy can diminish its benefits. Moreover, a firm’s AC will not positively moderate the curvilinear relationship between exploration and the firm’s innovative performance in all contexts, contradicting our theoretical predictions. This is due to the existence of trade-offs between AC characteristics and other organizational factors. Originality/value – This paper extends the understanding of Open Innovation and AC theories. Our results suggest that AC cannot be understood as a one-dimensional and autonomous capacity located exclusively in R&D departments. Aspects such as financial power, the business model and the different dimensions of AC and their respective locations in the firm’s value chain should be considered whenever the influence of AC on exploration strategies is analyzed.